PENGETAHUAN PERAWATAN KAKI DENGAN KEJADIAN ULKUS DIABETIKUM PADA PENDERITA DM TIPE II DI PUSKESMAS DARUSALAM, MEDAN - Ramadhani, Yuni; Situmorang, Helfrida (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Over time, the number of people with diabetes mellitus in the world has increased from year to year. The 2013 Basic Health Research (Riskesdas) data showed that there was an increase in the prevalence of diabetes in Indonesia from 5.7 percent (in 2007) to 6.9 percent or around 9.1 million people in 2013. will cause a variety of symptoms and complaints, and if not treated can cause various complications, both acute and chronic. One of the chronic complications that are often experienced by patients with type 2 diabetes is diabetic ulcers. Complications of diabetic ulcers will not occur if people with DM.The purpose of this study was to determine the relationship between knowledge of foot care and the incidence of diabetic ulcers in patients with type II diabetes in the working area of the Darusalam Public Health Center, Medan. This research is a descriptive study with a correlational approach with a sample of 30 people, where the data analysis is presented in the form of a frequency distribution and Speraman Rank test.The results obtained that the results of statistical tests using the correlation coefficient test with a significance of 0.003 or 0.003 > 0.05, the correlation coefficient value of 0.498 means that the relationship is quiteThe conclusion in this study is that there is a significant relationship between greetings and greetings with the level of patient satisfaction with health services at the Puskesmas Darusallam Health Center in 2021. It is expected that the staff when providing health services to patients always smile, greet, greet each patient so that there are expected to be patient satisfaction when getting health services at the puskesmas.